Pelaksanaan Promosi Melalui Media Sosial Instagram Pada Toko Zizara Depok - Isnurrini hidayat (Universitas Bina Sarana Informatika, 2017)
– Competition of companies should pay attention to its marketing system as a spearhead in dealing directly with the market. In the marketing mix, one of its main strategies is promotion. It is one of the early promotions in order to introduce a product to the consumer and this becomes very important as it relates to the benefits that will accrue to the company in terms of increasing product sales. In terms of promotions, Zizara Store has promoted material namely giveaway and some quiz in the instagram account. Research method used is observation, interview and documentation. The data used from the effectiveness of the implementation of the promotion is a period in February-March 2017. With the stages of the promotion so quickly attracted the attention of Zizara Store customers in social media. In the implementation of promotional advertising there are some products that have been damaged materials and late in uploading a photo of a product but Does not preclude promotional activities that have been done. ased on the results of the study it can be concluded that the effectiveness of the implementation of promotional advertising is already good, this is proven by the existence of a sales increase to 7%. Therefore the authors suggest the Zizara Store more attention to fabrics and can be made Procedure of Operational Standard for deadline photo upload.